AI empowered : pioneering African American entrepreneurship in the Digital Age - George, Babu; Wooden, Ontario S. (Emerald Publishing Limited, 2025)
With the rapid advancement of artificial intelligence (AI), new technology is reshaping business landscapes and creating unprecedented opportunities for innovation and growth. Professors Babu George and Ontario Wooden explore the transformative journey of African American entrepreneurs as they navigate the evolving AI era. Beginning with a conceptual analysis based on firsthand experiences with African American business leaders and supported by the existing literature, George and Wooden trace the historical trajectory of African American entrepreneurship, highlighting the resilience and ingenuity that have long defined this community. They examine critical aspects such as policy frameworks, financial strategies, educational initiatives, and the importance of networking within the AI ecosystem, underscoring the need for inclusive policies and accessible resources to ensure African American entrepreneurs can fully participate in and benefit from the AI revolution. At the heart of the discussion is AI's role in bridging socioeconomic divides, equipping African American entrepreneurs with powerful tools to overcome systemic barriers and advance toward economic empowerment. Through micro-case studies, innovative insights, and actionable strategies, the book brings home the hope that digital divides and systemic inequities can be overcome successfully. AI Empowered concludes with a forward-looking perspective, envisioning a future where African American entrepreneurs lead AI-driven innovation. It calls for a collective effort to support these trailblazers and foster a diverse, dynamic entrepreneurial landscape that reflects the promise of the digital age.
Includes index.
Keywords: African American businesspeople.; Computers -- Artificial Intelligence -- General.; Artificial intelligence.; elektronické knihy; electronic books